2017
DOI: 10.24187/ecostat.2017.494t.1920
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the effects of unconventional monetary policies on the cost of credit to non-financial companies in the eurozone

Abstract: The aim of this paper is to assess the effects of unconventional monetary policies (UMPs) on the cost of credit to non-financial companies in the eurozone. We analyse the direct effects of these UMPs using a multiple linear regression, then we seek to highlight the existence of a complementarity between these policies and the interest rate policy-an indirect effect of UMPs-using an interaction term. We show that the direct effects of UMPs are limited, indeed nil depending on the country, and are always weaker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Besides this extensive literature, only a few papers attempted at showing the link between non-financial corporations' investments in the EMU and the ECB's monetary policy. Kanga and Levieuge (2017) assess the effects of the different ECB's unconventional monetary policies on the cost of credit of non-financial firms in each EMU country. Daetz et al (2016) focus, albeit not exclusively, on the impact of the ECB's LTROs on non-financial firms' cash holdings and concluded that the ECB's measures were most beneficial to corporations from peripheral countries.…”
Section: The Ecb's Monetary Policies' Effects On Non-financial Firmsmentioning
confidence: 99%
“…Besides this extensive literature, only a few papers attempted at showing the link between non-financial corporations' investments in the EMU and the ECB's monetary policy. Kanga and Levieuge (2017) assess the effects of the different ECB's unconventional monetary policies on the cost of credit of non-financial firms in each EMU country. Daetz et al (2016) focus, albeit not exclusively, on the impact of the ECB's LTROs on non-financial firms' cash holdings and concluded that the ECB's measures were most beneficial to corporations from peripheral countries.…”
Section: The Ecb's Monetary Policies' Effects On Non-financial Firmsmentioning
confidence: 99%